Histomorphometric analysis of pure titanium implants with porous surface versus rough surface Análise histomorfométrica de implantes de titânio puro com superfície porosa versus superfície rugosa - Aline Scalone Brentel; Luana Marotta Reis de Vasconcellos; Marize Varella Oliveira; Mário Lima de Alencastro Graça; Luis Gustavo Oliveira de Vasconcellos; Carlos Alberto Alves Cairo; Yasmin Rodarte Carvalho (University of São Paulo, 2006)
The purpose of this study was to analyze the bone repair around commercially pure titanium implants with rough and porous surface, fabricated using powder metallurgy technique, after their insertion in tibiae of rabbits. Seven male rabbits were used. Each animal received 3 porous-surface implants in the left tibia and 3 rough-surface implants in the right tibia. The rabbits were sacrificed 4 weeks after surgery and fragments of the tibiae containing the implants were submitted to histological and histomorphometric analyses to evaluate new bone formation at the implant-bone interface. Means (%) of bone neoformation obtained in the histomorphometric analysis were compared by Student's t-test for paired samples at 5% significance level.. The results of the histological analysis showed that osseointegration occurred for both types of implants with similar quality of bone tissue. The histomorphometric analysis revealed means of new bone formation at implant-bone interface of 79.69 ± 1.00% and 65.05 ± 1.23% for the porous- and rough-surface implants, respectively. Statistically significant difference was observed between the two types of implants with respect to the amount new bone formation (p<0.05). In conclusion, the porous-surface implants contributed to the osseointegration because they provide a larger contact area at implant-bone interface. O propósito deste estudo foi avaliar a reparação óssea ao redor de implantes de superfície porosa comparados com implantes de superfície rugosa, ambos confeccionados de titânio puro grau 2 por meio da técnica de metalurgia do pó. Os implantes foram inseridos em tíbias de coelhos. Foram utilizados neste estudo 7 coelhos machos, sendo que cada um recebeu 3 implantes de superfície porosa na tíbia esquerda e 3 implantes de superfície rugosa na tíbia direita. Os animais foram sacrificados 4 semanas após a cirurgia e os fragmentos das tíbias contendo os implantes foram submetidos à análise histológica e histomorfométrica, visando analisar a neoformação óssea na interface osso-implante. As médias (%) obtidas na análise histomorfométrica foram avaliadas por meio do teste estatístico t-student de amostras pareadas com nível de significância de 5%. Os resultados da análise histológica mostraram que a osseointegração foi obtida nos dois tipos de implantes com similar qualidade de tecido ósseo. Na análise histomorfométrica, verificaram-se médias de neoformação óssea na interface osso-implante de 79,69% ± 1,00 e 65,05 ± 1,23 para os implantes de superfície porosa e rugosa, respectivamente, e foi observada diferença estatisticamente significante entre os dois tipos de implantes com relação à quantidade de neoformação óssea. Concluiu-se que os implantes de superfície porosa contribuíram para a osseointegração devido à sua maior superfície de contato na interface osso-implante.